The Impact and Practice of Interdisciplinary Approaches on School Physical Education - Ming Han Feng; Gang Song (International Journal of Education and Humanities, 2025)
With the advancement of the core competency education concept, the transformation of school physical education (PE) has become a crucial issue in China’s education reform. Traditional PE teaching, which often focuses narrowly on skill acquisition and physical performance, faces limitations in cultivating students’ comprehensive competencies. In response, interdisciplinary teaching has emerged as a key strategy to enhance both the depth and breadth of learning experiences in PE. The purpose of this study is to explore the influence and implementation models of interdisciplinary approaches within the framework of China’s Compulsory Education Physical Education and Health Curriculum Standards (2022 Edition). Using a combination of theoretical analysis and practical case studies, this research investigates how thematic integration, technology-enhanced learning, and innovative assessment systems can enrich the PE learning process. The findings reveal that interdisciplinary methods not only strengthen students’ athletic participation and interest but also promote cognitive understanding, emotional engagement, and value-based development. Furthermore, the integration of digital tools and cross-subject collaboration enhances the relevance and adaptability of PE in contemporary education. Several challenges remain, including disciplinary boundaries, insufficient teacher preparedness, and technological implementation difficulties. The study suggests that future development should emphasize building problem-oriented interdisciplinary communities, enhancing professional training for teachers, and improving technological infrastructure. These measures will support the evolution of PE toward a more integrated, intelligent, and student-centered pedagogical model that aligns with the goals of holistic education and sustainable learning development